Condition Report: : Symposium on Building Art Institutions in Africa - Ayim, Nana Oforiatta; Beckhurst, Gabriella; Bell, Marilyn Douala Manga (text); Chapelle, Adeline; Karroum, Abdellah (text); Kouoh, Koyo; Njami, Simon (text); Rifky, Sarah (text); Schaub, Didier (text); Verges, Francoise (text); Kouelany, Bill; Ngcobo, Gabi; et al. (Dakar; RAW Material Company; Hatje Cantz Verlag, 2013)
Condition Report: Symposium on Building Art Institutions in Africa is a collection of essays resulting from of the symposium held in Dakar in 2012. They address the changing role of art institutions and initiatives in Africa, where the cultural and artistic context is characterized by a predominance of government led art programs and infrastructure. The last decade has witnessed the emergence of a variety of independent art spaces using a wide range of formats to promote art and critical exchange. These initiatives draw a new cartography of artistic action in Africa. This reader looks at the structural and programmatic issues at play within those institutions. Models and profiles of art institutions developed in other regions of the world are also examined. The publication also discusses how former colonial powers define and implement their strategies of cultural representation and exchange in post-colonial areas, and how these in turn influence local dynamics of cultural action. Funded by the German Federal Cultural Foundation and the Goethe-Institut.
CONTENTS: -- 1. Foreword/ Hortensia Volckers & Katharina von Ruckteschell -- 2. Introduction/ Koyo Kouoh -- 3. Filling the Voids. The Emergence of Independent Contemporary Art Spaces in Africa/ Koyo Kouoh -- 4. Imagined Communities/ Simon Njami -- 5. The Story of my history of L'appartement/ Abdellah Karroum -- 6. Mapping 'Invisible Lives'/ Francoise Verges -- 7. Continuous Invention: A Duty and a Necessity/ Didier Schaub & Marilyn Douala Manga Bell -- 8. On Instituting a New Space for Thought. This Place is called Beirut/ Sarah Rifky -- 9. Fiction is a Serious Matter/ Adeline Chapelle & Bill Kouelany -- 10. Endnotes. Was it a question of power?/ Gabi Ngcobo -- 11. Ideal Space for Contemporary Art/ Sunjung Kim -- 12. New Funding Models. A message from New York/ Yona Backer -- 13. We cannot create a Map of a Terrain that doesn't exist yet at best we can make a Weather Prediciton/ Anne Szefer Karlsen -- 14. Conditioned Networks/ Juan A. Gaitan -- 15. We Want to Take Part/ Katharina von Ruckteschell -- 16. Art Without Education/ Anton Vidokle -- 17. The Poetics of the Infra-ordinary. The Aesthetic of Recognition in Contemporary African Art- Elvira Dyangani Ose -- 18. New Relativities of Art/ Nana Oforiatta-Ayim -- 19. A Different Reality of Networking/ Oumar Sall
English; French
Keywords: Contemporary Art; N4390-5098 Visual Arts. Exhibitions; Africa